2022
DOI: 10.1111/oik.09313
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization shapes the relation between density and melanin‐based colouration in bird communities

Abstract: Growing urbanization increasingly influences ecosystems worldwide. While the effects of urban conditions within species (through either plastic or evolutionary responses) have been widely studied, their potential influences among species (through environmental filter), especially concerning their colouration, remain poorly known. Here, we investigated whether avian communities breeding inside and outside a major European city (Paris) differ with regards to melanin‐based plumage colouration. Melanins are herita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…Additionally, a recent study suggested that melanic birds (i.e. species with blackish colors) may thrive in urban assemblages due to the protective properties of melanin pigments, which can enhance resistance to tissue abrasion, higher temperatures, and detoxification of toxic metals commonly found in urban air pollution (Turak et al 2022). Megacolorful birds might thus not thrive in urban environments due to their low resistance to the damaging effects of urban pollution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a recent study suggested that melanic birds (i.e. species with blackish colors) may thrive in urban assemblages due to the protective properties of melanin pigments, which can enhance resistance to tissue abrasion, higher temperatures, and detoxification of toxic metals commonly found in urban air pollution (Turak et al 2022). Megacolorful birds might thus not thrive in urban environments due to their low resistance to the damaging effects of urban pollution.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates based on nighttime lights and artificial impervious areas show that urban land cover has increased over the last 30 years and now covers 0.5-0.7% (ca. 800,000 km 2 ) of the total land surface on Earth (Gong et al 2020, Zhao et al 2022. Moreover, global projections of urban land cover over the 21st century suggest that the total amount of urban land will further increase by a factor of 1.8-5.9, with the fastest urban land expansion occurring in the tropics (Seto et al 2012, Gao et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Bird color diversity has recently been analyzed along urbanization gradients, and sites dominated by buildings were clustered compared to null models, being dominated by bird species with grey or dark colors (Leveau, 2019;Turak et al, 2022). Grey plumage may enhance bird camouflage with impervious grey surfaces (Leveau, 2019).…”
Section: Introductionmentioning
confidence: 99%